Biomass allocation of tidal freshwater marsh species in response to natural and manipulated hydroperiod in coastal deltaic floodplains. (5th May 2022) - Rovai, Andre S.; Twilley, Robert R.; Christensen, Alexandra; McCall, Annabeth; Jensen, Daniel J.; Snedden, Gregg A.; Morris, James T.; Cavell, John A.
Abstract: Deltaic floodplains are highly vulnerable to relative sea level rise (RSLR) depending on the sediment supply from river channels that provides elevation capital as adaptation mechanism. In river channels where levees have restricted sediment supply to coastal deltaic floodplains, river sediment diversions have been proposed as a restoration strategy to increase elevation allowing for marshes to establish and cope with RSLR. The response of coastal wetlands to surface elevation has been well-defined for estuarine marshes, but models for coastal deltaic floodplain marshes have not been resolved. Here we coupled field observations from biomass plots and a mesocosm experiment ('marsh organ') with remote sensing techniques to assess biomass allocation of tidal freshwater marsh species in response to gradients in hydroperiod in Wax Lake Delta (WLD), coastal Louisiana, U.S.A.. We found that, contrary to salt-tolerant species, Colocasia esculenta aboveground biomass (AGB) is strongly positively correlated with percent inundated time (R 2  = 0.79, P  < 0.001), increasing from (mean ± 1SE) 186 ± 69 g/m 2 in the supratidal zone to 1422 ± 148 g/m 2 beyond its natural occurrence range in the lower intertidal zone. Belowground biomass consistently exceeded AGB at 2363 ± 294 g/m 2 on average across elevation treatments. We also found that C. esculenta expanded its surface coverage area by 31% in five years consistent with the growth and emergence of WLD's subaqueous platforms, reflecting this species ability to cope with higher inundation time. In contrast to earlier studies conducted in brackish and saline settings, where longer hydroperiods had negative effects on biomass accumulation, our data suggest that tidal freshwater marshes can cope with longer hydroperiods caused by river sediment diversions. Highlights: Tidal freshwater marshes are adapted to broader surface elevation ranges. Hydrogeomorphic zones control tidal freshwater marsh distribution and production. Colocasia esculenta biomass increased with percent inundation time. Tidal freshwater marshes track and speed deltaic islands' expansion and elevation gain. Ecogeomorphic feedbacks following river sediment diversions help sustain stable shorelines.